Radical radiotherapy for squamous cell carcinoma of the larynx - comparison of three-dimensional conformal radiotherapy with cobalt-60 teletherapy - Krstevska, Valentina; Stojkovski, Igor; Zafirova Ivanovska, Beti (My University, 2011)
The aim of the study was to report the results of radical radiotherapy performed by three-dimensional conformal radiotherapy (3DCRT) for squamous cell carcinoma of the larynx and to compare these data with those obtained with two-dimensional radiotherapy (2DRT) realized with cobalt-60 teletherapy i.e. telecobalt therapy (TCT). Eighty patients with previously untreated laryngeal cancer were irradiated with curative intent at the University of Radiotherapy and Oncology Clinic (UCRO) in Skopje between February 1999 and December 2008. Radical radiotherapy with the TCT unit was performed on 38 patients between February 1999 and May 2005. From June 2005 to December 2008, 42 patients were treated with a linear accelerator using 3DCRT. Complete response rates three months after completion of radiotherapy were 84.2% (32 of 38) and 92.6% (39 of 42) in the group irradiated with TCT unit and in the group treated with 3DCRT, respectively. No statistically significant differences were observed either in locoregional control (LRC) or overall survival (OS) between the patients treated with two different radiotherapy techniques. The grade of acute reactions of the skin and the larynx differed significantly between the accomplished radiotherapy techniques (Nonparametric Mann-Whitney U Test; U=577.0; Z=-2.129; p=0.012, and U=497.0; Z=-2.90; p=0.001, respectively). There were statistically significant differences observed in the grade of late effects in the skin and in the subcutaneous tissue between the radiotherapy techniques used (Nonparametric Mann-Whitney U Test; U=425.0; Z=-3.593; p=0.001 and U=637.0; Z=-1.551; p=0.035, respectively). According to the confirmed advantage of 3DCRT in terms of reduced treatment toxicity observed in our study, we consider conformal techniques being a basis in definitive radiotherapy of squamous cell carcinoma of the larynx until the new revolutionary techniques will be clinically available.
Keywords: laryngeal carcinoma; three-dimensional conformal radiotherapy